Polyoma virus DNA replication is semi-discontinuous. - Hendrickson, E A (1987)
In marked contrast to simian virus 40 (SV40), polyoma virus (PyV) has been reported to replicate discontinuously on both arms of replication forks. In an effort to clarify the relationship between the mechanisms of DNA replication in these closely related viruses, the distribution of RNA-primed DNA chains at replication forks was examined concurrently in PyV and SV40 replicating DNA purified from virus-infected cells. About one third of PyV DNA chains contained 7 to 9 ribonucleotides covalently linked to their 5'-end. A similar fraction of DNA chains from replicating SV40 DNA contained an oligoribonucleotide that was 6 to 9 residues long and began with either (p)ppA or (p)ppG. Greater than 80% of PyV or SV40 RNA-primed DNA chains hybridized specifically to the retrograde template. Moreover, at least 95% of the RNA-primed DNA chains from either PyV or SV40 whose initiation sites could be mapped to unique nucleotide locations originated from the retrograde template. Therefore, PyV and SV40 DNA replication forks are essentially the same; DNA synthesis is discontinuous predominantly, if not exclusively, on the retrograde template.